2022
DOI: 10.1186/s40001-022-00789-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between sex and outcomes in patients with non-small-cell lung cancer receiving combination chemoimmunotherapy as a first-line therapy: a systematic review and meta-analysis of randomized clinical trials

Abstract: Introduction Recently, several meta-analyses have investigated the association between sex and the efficacy of immune checkpoint inhibitors (ICIs) in non-small-cell lung cancer (NSCLC). However, this issue remains controversial, because the results have been inconsistent. Moreover, the effect of sex on outcomes in patients with NSCLC receiving combination chemoimmunotherapy as a first-line therapy is poorly understood. The aim of this study was to examine the association between sex and outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…Previous reports of improved SOR for females in NHL/rituximab were generated from single trials or anecdotal evidence collected from a few trials 56 , but the sex-preference in response to rituximab has not been systematically reported across trials. Importantly, other anecdotal reports of sex differences for various malignancy/treatment combinations 25 , 31 , 57 , 58 are not supported by our analysis of all oncology trials. Notably, rituximab does not show consistently better outcomes in females across other B-cell disorders 59 , suggesting that oncology clinical trials may reflect an interaction of NHL and rituximab with sex specificity, rather than a sex-specific pharmacodynamic property 60 .…”
Section: Discussioncontrasting
confidence: 88%
“…Previous reports of improved SOR for females in NHL/rituximab were generated from single trials or anecdotal evidence collected from a few trials 56 , but the sex-preference in response to rituximab has not been systematically reported across trials. Importantly, other anecdotal reports of sex differences for various malignancy/treatment combinations 25 , 31 , 57 , 58 are not supported by our analysis of all oncology trials. Notably, rituximab does not show consistently better outcomes in females across other B-cell disorders 59 , suggesting that oncology clinical trials may reflect an interaction of NHL and rituximab with sex specificity, rather than a sex-specific pharmacodynamic property 60 .…”
Section: Discussioncontrasting
confidence: 88%
“…21 More recently, several update meta-analyses also reported that female patients had a greater treatment outcomes improvement than male patients. [22][23][24] Consistently, this study analyzed 175 patients with untreated advanced or metastatic NSCLC received PD-1 blockade plus chemotherapy or chemotherapy and also observed that female patients derived a larger benefit from first-line PD-1 blockade in combination with chemotherapy, but not chemotherapy, than male patients. Taken together, these findings suggest that female patients with untreated advanced or metastatic NSCLC could derive a larger benefit from PD-1 blockade plus chemotherapy.…”
Section: Discussionmentioning
confidence: 63%
“…Data from single-agent ICIs studies are disappointing, but globally it seems that ICIs may result more effectively in men than women; perhaps because tumours in men are potentially more immunogenic given a higher mutational burden [178]. Conversely, a systematic review and meta-analysis of randomized clinical trials showed that a greater improvement in OS and PFS was observed in female patients than in male patients with combination chemoimmunotherapy as a first-line therapy [179]. However, available evidence is not strong enough to influence treatment choices; an insufficient number of studies analyze data by sex in a prospective and pre-planned manner.…”
Section: Discussionmentioning
confidence: 99%